HUBUNGAN DUKUNGAN KELUARGA DAN EFIKASI DIRI DENGAN MOTIVASI LANSIA DALAM MENGONTROL GLUKOSA DARAH PADA LANSIA DENGAN DIABETES MELITUS DI PUSKESMAS KINOVARO - Irmawati, Irmawati; Wahyu Kindang, Ismunandar; Marnianti Irnawan, Sri (Universitas Kadiri, 2023)
Family support is the accepting attitude of the family towards family members such as caring, supporting or providing help if needed, but self-efficacy is an assessment of an individual's ability to organize and perform the intervention needed to achieve certain performance goals. The elderly motivation is a psychological characteristic of the elderly in contribution to the level of their self-commitment. The aim of the research was to analyze the correlation between family support and self-efficacy with the elderly motivation of elderly with diabetes mellitus in controlling their blood sugar level at Kinovaro Health Center. This is quantitative research with an analytic approach and using a cross-sectional design. The total population was 176 elderly with diabetes mellitus at the Kinovaro PHC and the total sample was 64 respondents obtained by the Slovin formula and taken by using purposive sampling technique. The results of research of 64 respondents showed that there was a significant correlation between family support and elderly motivation found a p-value = 0.000 and there was a significant correlation between self-efficacy and elderly motivation found a p-value = 0.001. The conclusion mentioned that there is a correlation between family support and self-efficacy with the motivation of elderly with diabetes mellitus in controlling blood sugar levels at Kinovaro Public Health Center. Suggestions for Kinovaro Public Health Center officers to provide education about the importance of family support and self-efficacy to optimize the achievement of success in controlling blood sugar levels.